Effect Of Tournament Team Games Team Learning Model On Learning Learning Results - Gian Rahmat Ramadhan (Journal of Physical Education and Sport Science, 2019)
The long jump material, has been taught at the high school, junior high school level even at the elementary level, although the level began to be taught in grade IV elementary school. This makes the teacher must be more observant and creative in choosing a method and model of learning that is good for students, so that students can know, practice safely, and have enthusiasm in learning long jumps. As for the purpose of this study is to prove the truth Game Tournament Team learning model on learning outcomes squat style long jump in fourth grade students of SDN I Purwawinangun Kuningan Regency. The method of research used in this study is the experimental method, because this method is considered valid by some experts to uncover causal relationships. The Experimental Method is interpreted as a research method used to look for treatment effects on others in controlled conditions. Samples of Class IV male students at SD Negeri I Purwawinangun Kuningan Regency were 20 experimental groups and 20 control groups, and were selected using purposive sampling techniques technique. The conclusion of this study is that based on the results of processing and analysis of the research data and in accordance with the hypothesis that the authors propose, the results of the study can be discussed as follows. The first hypothesis states, "there are significant differences between before and after applying the Team Games learning model Tournament on the learning outcomes of the long jump on students of Purwawinangun 1 Elementary School Kuningan District. The results of the hypothesis are accepted, this is evidenced by the results of the data after testing the hypothesis in the final test, showing a significance value of 0,000. This does not mean that the study failed because the significance value was "0", but 0,000 was smaller than 0.05 (0,000 <0, 05). Because 0,000 is smaller than 0.05 means that there is a significant difference between before.